The Existence of Obesogenic Environmental Exposure to Obesity in Adolescents Aged Over 15 Years in DKI Jakarta: A Literature Study - Fatima Tudzahro; Nelsi Merella; Apriningsih Apriningsih (Jurnal Indonesia Sosial Sains, 2026)
Obesity in adolescents is a growing health problem, particularly in urban areas such as Jakarta, characterized by a modern and instantaneous environment. Obesogenic environments are characterized by high access to fast food, increased sedentary behavior, low physical activity, and easy use of digital services, which encourage unhealthy lifestyle changes. This study aims to examine the existence of obesogenic environmental exposure on obesity incidence in adolescents aged 15 years and over through a literature review of 10 national and international journals published between 2021 and 2026. The results of the review indicate that obesogenic environmental factors are closely related to the increased risk of obesity in adolescents. Consumption of high-calorie foods, sugary drinks, fast food habits, and low physical activity are dominant factors contributing to weight gain. In addition, socioeconomic factors, the urban environment, peer influence, and easy access to online food delivery services also reinforce the formation of sedentary behavior in adolescents. Adolescents living in urban areas tend to be more susceptible to obesity than adolescents in rural areas due to high exposure to a practical lifestyle and minimal physical activity. Thus, obesogenic environments play a significant role in increasing the prevalence of obesity among adolescents aged 15 and over in Jakarta. Therefore, promotional and preventive efforts are needed through health education, increased physical activity, and the creation of an environment that supports healthy lifestyles to reduce obesity rates among adolescents.